RESPON TANAMAN SELEDRI (APIUM GRAVIOLENS L.) TERHADAP PEMBERIAN PUPUK BOKASHI PADA UMUR BIBIT YANG BERBEDA - WAYAN LANA; ANAK AGUNG GEDE PUTRA; I NENGAH KARNATA (GANEC SWARA, 2022)
The purpose of this study was to determine the effect of bokashi fertilizer dose and seedling age and their interaction on the growth and yield of celery plants. This research was conducted in Banjar Candikuning 2, Candikuning Village, Baturiti District, Tabanan with an altitude of 1255 m above sea level. The study was conducted from November 22, 2021 to January 26, 2022. This research is a pot experiment using a basic design, namely Randomized Block Design with a factorial pattern. The treatments given were the dose of bokashi fertilizer and the age of the seedlings, each treatment was repeated three times.The interaction between bokashi fertilizer dose treatment and seedling age (N x U) had a very significant effect (P < 0.01) on most of the observed parameters, except for the oven dry weight of the top of the plant, oven dry weight of the bottom of the plant and oven dry weight. total plants that showed no significant effect (P 0.05). The highest total plant fresh weight was obtained at a dose of 1.0 kg of bokashi fertilizer at the age of 25 days after seedling (N2U1) of 7.40 g, an increase of 482.67% from the lowest yield of treatment with a dose of bokashi fertilizer without fertilizer at the age of 30 seeds. hss (N0U2) which is 1.27 g.Bokashi fertilizer treatment with a dose of 1.0 kg (N2) gave the highest total plant oven dry weight of 0.44 g, while the lowest was obtained in the treatment without fertilizer (N0) only 0.09 g or an increase in yield of 388.89 %. The seedling age treatment gave the highest total oven dry weight of the plant at the seedling age of 25 hss (U1) which was 0.35 g or an increase in yield of 45.83% compared to the 30 hss (U2) seedling age treatment which gave the total oven dry weight of the plant only. of 0.24 g